2013
DOI: 10.1002/marc.201300060
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline–Polypyrrole Composites with Enhanced Hydrogen Storage Capacities

Abstract: A facile method for the synthesis of polyaniline-polypyrrole composite materials with network morphology is developed based on polyaniline nanofibers covered by a thin layer of polypyrrole via vapor phase polymerization. The hydrogen storage capacity of the composites is evaluated at room temperature exhibits a twofold increase in hydrogen storage capacity. The HCl-doped polyaniline nanofibers exhibit a storage capacity of 0.46 wt%, whereas the polyaniline-polypyrrole composites could store 0.91 wt% of hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The completion of the reaction was checked by thin layer chromatography (TLC) in mixture of hexane and ethyl acetate (1:9). After completion of the reaction, the solvent was removed under reduced pressure to get the product i.e., cyanoethyl tetrazole acetic acid [1][2][3][4][5][6][7][26][27][28][29][30][31][32]. Then, the obtained compound was taken in acetonitrile (30 mL) and equimolar bromobutane was added to the above solution with stirring.…”
Section: Preparation Of Tetrazolium or Tetrazole Ring Based Ionic Liqmentioning
confidence: 99%
See 2 more Smart Citations
“…The completion of the reaction was checked by thin layer chromatography (TLC) in mixture of hexane and ethyl acetate (1:9). After completion of the reaction, the solvent was removed under reduced pressure to get the product i.e., cyanoethyl tetrazole acetic acid [1][2][3][4][5][6][7][26][27][28][29][30][31][32]. Then, the obtained compound was taken in acetonitrile (30 mL) and equimolar bromobutane was added to the above solution with stirring.…”
Section: Preparation Of Tetrazolium or Tetrazole Ring Based Ionic Liqmentioning
confidence: 99%
“…It is because of both fundamental interest and potential applications in the, electro-chromic devices, energy storage and conversion systems, sensors anticorrosive coatings, and electro-catalysts etc. [1][2][3][4][5][6]. Some of the conducting polymers are soluble in water and/ or in organic solvents, which facilitates their application on surfaces as a thin film is one of the interesting property [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the mechanism of hydrogen uptake in these materials is still not fully understood, and the role of the π ‐electron system backbone and charge transfer in hydrogen uptake still needs to be elucidated. Recently, we have investigated the hydrogen storage properties of polyaniline–PPY composites and the effect of dopant and dopant counter‐anion size on the hydrogen storage capacity and mechanism . Also developed has been nanoporous PPY with internal pockets and pores prepared using solid‐state vapor‐phase polymerization and the hydrogen adsorption properties have been studied …”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have described the purification, individuation and dispersion of CNTs . These experiments drew on our experience of the conducting polymer PPY . In the study reported here, we synthesized PPY‐NPs using a facile chemical oxidative polymerization method, and then synthesized nanocomposites from the PPY‐NPs with CNTs (PPY‐NP‐CNTs) using single‐walled carbon nanotubes (SWNTs) and multi‐walled carbon nanotubes (MWNTs), which were first dispersed using various surfactants.…”
Section: Introductionmentioning
confidence: 99%